Hepatic Injury Induced by Dietary Energy Level via Lipid Accumulation and Changed Metabolites in Growing Semi-Fine Wool Sheep - Xue, Benchu; Hong, Qionghua; Li, Xiang; Lu, Mingli; Zhou, Jia; Yue, Shuangming; Wang, Zhisheng; Wang, Lizhi; Peng, Quanhui; Xue, Bai (Frontiers in Veterinary Science, 2021)
Liver, as the core organ of animal body, the injury it suffered threatens the whole health of organism. The metabolism of liver was affected by numerous factors, and dietary energy level is the crucial one. Therefore, the aim of the present study is to evaluate hepatic injury and illustrate the metabolic mechanism in ruminants fed diets with different dietary energy level. Twenty-five Yunnan semi-fine wool sheep were randomly assigned to five groups, fed with five dietary metabolic energy level: 1) low energy (LE); 2) Medium low energy (MLE); 3) Medium energy (ME); 4) Medium high energy (MHE); 5) High energy (HE). As results shown, the lipid droplets AOD of LE, MLE and HE group were higher than that in ME, MHE group. The enzyme activity of ALT reached the lowest in ME group. The increasing dietary energy level promoted the SOD, GSH-Px activities, and changed the MDA, PCO contents quadratically. In addition, the high and low dietary energy level both upregulated the mRNA abundance of proinflammatory cytokine IL-1β, Nfkb and TNF-α. In the results of metabonomics, compared with ME group, 142, 77, 65, and 108 differential metabolites were detected in LE, MLE, MHE and HE groups respectively. These metabolites were involved in various biochemical pathways, such as glycolipid metabolism, bile acid metabolism, lipid metabolism etc. In conclusion, the high and low dietary energy level caused the various forms of hepatic injury. The results of section-staining and metabonomics showed that the reason may be the changed metabolism status and lipid accumulation induced by lipid mobilization.